ANALISIS PENGEMBANGAN KOMUNITAS DALAM PROGRAM INTERVENSI BERBASIS MASYARAKAT OLEH BADAN NARKOTIKA NASIONAL (BNN) JAKARTA TIMUR - Ricardo S, David (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The Community Based Intervention Program (IBM), designed by the National Narcotics Agency (BNN), aims to address drug abuse by involving the community in interventions for individuals misusing drugs in East Jakarta. This study evaluates the community development processes implemented by BNN to ensure the sustainability of IBM and identifies the factors influencing this development. The research employs a descriptive qualitative approach, utilizing observations and interviews with relevant informants. The findings indicate that community development within the IBM program is progressing well, despite some challenges. Key components developed include empowerment, network strengthening, and sustainability. Identified supporting factors encompass community assets and potentials, community participation, leadership, and partnership networks, while the use of technology still faces obstacles. A significant finding is the importance of communication both direct and through other media in building relationships among individuals and achieving IBM's objectives. This insight presents an opportunity for BNN to formulate more effective communication strategies. To ensure the continued success of the IBM program, it is recommended to conduct regular and transparent evaluations so that all stakeholders can track its progress.